Methods and Techniques of Emphasis in Shahnameh: The Case of Kamoos Koshani Story - Elham Farmahini Farahani; Hassan Heidary; Ali Sabbaqi (Literary Arts, 2021)
Abstract In literary texts, some sentences are more important than others and are thus, highlighted through emphasis. The current study aims at reviewing 3000 verses from Shahnameh to extract the methods and techniques of emphasis. The researcher seeks to find out what structural, rhetorical, or semantic devices are used in the Kamoos Keshani story to show emphasis. The data was collected deductively, and the data analysis was descriptive-analytic. This study categorized the emphasis in Shahnameh into two types: general emphasis and specific emphasis. General emphasis consists of reiteration, apposition, description, hyperbole, contrast, opposition, and limitation. Reiteration is an artistic repetition of the exact words, meanings, synonyms, and a combination of words and meanings. The combination occurs in the repetition of nouns, noun phrases, adjectives, adverbial clauses, and objects. The repetition of meaning or synonym consists of a semantic synonym of two verses. The emphasis of apposition happens through a series of consecutive words. In this study, the words such as 'many', 'hard', 'much', and 'numerous' are known as descriptive. These words function as adjectives if they follow a noun and function as an adverb if they follow a verb. Hyperbole and other related terms such as exaggeration have an implied usage in epics. In Shahnameh, other devices of emphasis are usually along with hyperboles. The second type of emphasis is the specific emphasis which happens through using nouns, inclusion, connecting pronouns, verbs, propounding the verb, prosody, sentence emphasis, sounds, rhetorical questions,  interjections, redundancy,  condition, omitting connectors, emphasis without devices, as well as emphasis through analogy and irony. Also, a transition of the sentence constituents can affect emphasis. The noun emphasis in Shahnameh happens through appositive pronoun, and the inclusion emphasis happens through words such as 'purity', 'thoroughly', 'all', 'anybody', 'anything', 'every', and 'everyone'. The exemplar connectors, in Shahnameh, are only 'particular' and 'in particular'. The techniques of pronoun emphasis are similar to those of noun emphasis. The verb emphasis happens through the verbs with the comparative and superlative adjectives, adverbs, and swears. Moreover, propounding the verb is one of the main techniques of emphasis in Shahnameh. The prosodic emphasis in Shahnameh mostly occurs with the word 'remorse'. Adverbs such as 'correctly' and 'inevitably' are used for the sentence emphasis, and 'never' and 'no' for emphasizing verbs such as 'prohibit' and 'forbid'. Redundancy is also another technique that occurs in Shahnameh based  to show emphasis.